A retrospective study of autologous hematopoietic stem cell transplantation for peripheral T-cell lymphoma: pre-transplant patients with partial remission benefit from post-transplant maintenance therapy - Huang, Zhenghua; Li, Zhen; Wang, Juan; Gui, Ruirui; Zu, Yingling; Yu, Fengkuan; Lin, Quande; Zhao, Huifang; Zhang, Yanli; Fang, Baijun; Liu, Yanyan; Zhou, Keshu; et al. (Frontiers in Oncology, 2023)
Whether autologous hematopoietic stem cell transplantation (ASCT) improves the survival of patients with peripheral T-cell lymphoma (PTCL) remains controversial. Some studies have demonstrated that the efficacy of ASCT is superior in patients with complete remission (CR), whereas patients with partial remission (PR) remain vulnerable to relapse after ASCT, resulting in decreased survival rates. Maintenance therapy after chemotherapy may reduce the relapse rate of PTCL and improve survival; however, the role of maintenance therapy after ASCT in PTCL remains unclear. In this study, we aimed to analyze the efficacy of ASCT and post-transplant maintenance therapy in PTCL. We retrospectively analyzed the clinical data of 69 patients with PTCL who underwent ASCT at our center between November 2001 and November 2021. At a median follow-up of 36 months, the entire cohort’s 3-year overall survival (OS) and progression-free survival (PFS) were 67.8% and 53.0%, respectively. The 3-year OS and PFS of patients with CR1, CR2, and PR were 85.3% and 65.4%, 80.0% and 60.0%, and 38.4% and 32.0%, respectively (OS: P=0.001; PFS: P=0.003). Thirty patients received post-transplant maintenance treatment, whereas 39 did not. The relapse rates between the group with or without maintenance therapy were 26.7% vs. 52.2%, the 3-year OS was 86.0% vs. 54.2% (P=0.004), and the 3-year PFS was 73.3% vs. 37.5% (P=0.004). Further analysis revealed that the efficacy of maintenance therapy was not significant in patients with CR1 and CR2, whereas patients with PR benefited from maintenance therapy. The relapse rate of patients with PR who received or did not receive maintenance therapy was 33.3% vs. 78.7%, 3-year OS was 66.7% vs. 21.9% (P=0.007), and 3-year PFS was 66.7% vs. 12.5% (P=0.004). In conclusion, patients with CR in PTCL benefit from ASCT, and post-transplant maintenance therapy reduces the relapse rate and significantly improves OS and PFS in patients with PR.